2013
DOI: 10.3310/hta17130
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the psychological consequences of false-positive screening mammograms

Abstract: Reports are published in Health Technology Assessment (HTA) if (1) they have resulted from work for the HTA programme, and (2) they are of a sufficiently high scientific quality as assessed by the reviewers and editors.Reviews in Health Technology Assessment are termed 'systematic' when the account of the search appraisal and synthesis methods (to minimise biases and random errors) would, in theory, permit the replication of the review by others. HTA programmeThe HTA programme, part of the National Institute f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
108
1
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(118 citation statements)
references
References 141 publications
2
108
1
7
Order By: Relevance
“…[24][25][26][27] These findings, however, generally indicate that minimal to moderate levels are reported during the screening process but subsequently decrease upon receipt of a non-cancerous finding. [24][25][26][27] Similar to other cancer types, participants in the present study experienced moderate levels of distress prior to being screened for lung cancer. However, unlike the published reports for breast and colon cancers, elevated distress scores were maintained among approximately 1/3 of the study's lung cancer screening patients, despite receipt of a non-concerning finding.…”
Section: Discussionmentioning
confidence: 60%
“…[24][25][26][27] These findings, however, generally indicate that minimal to moderate levels are reported during the screening process but subsequently decrease upon receipt of a non-cancerous finding. [24][25][26][27] Similar to other cancer types, participants in the present study experienced moderate levels of distress prior to being screened for lung cancer. However, unlike the published reports for breast and colon cancers, elevated distress scores were maintained among approximately 1/3 of the study's lung cancer screening patients, despite receipt of a non-concerning finding.…”
Section: Discussionmentioning
confidence: 60%
“…23,32 The third limitation is that about 8% of the biopsy data are estimated to be missing from the ASR database. This could lead to a slight underestimation of the odds of fail-torescreen for women who had benign biopsies, which means the reported effect size is likely to be conservative.…”
Section: Discussionmentioning
confidence: 99%
“…Both studies found significantly lower retention rates, 66.5% (Spain) and 45.8% (Alberta) for those who underwent invasive procedures, including aspiration, closed biopsy and/or open biopsy. 22 Invasive follow-up tests have been shown to create psychological distress in the context of false positive breast cancer screens, 23 which can last for up to three years; 7,24 it is likely that psychological distress plays an important role in screening retention.…”
Section: Discussionmentioning
confidence: 99%
“…37 One study found that 30% of recalled women felt very anxious on receipt of their recall letter, whilst another study reported that 40% of women reported feeling very frightened when they received their recall letter. 38,39 16% of respondents felt certain that they had breast cancer.…”
Section: Psychological Impact Of Recallmentioning
confidence: 99%